2H→1T Phase Engineering of Layered Tantalum Disulfides in Electrocatalysis: Oxygen Reduction Reaction - Luxa, Jan; Mazánek, Vlastimil; Pumera, Martin; Lazar, Petr; Sedmidubský, David; Callisti, Mauro; Polcar, Tomáš; Sofer, Zdeněk (Chemistry (Weinheim an der Bergstrasse, Germany), 2017)
Tremendous attention is currently being paid to renewable sources of energy. Transition-metal dichalcogenides (TMDs) have been intensively studied for their promising catalytic activities in the hydrogen evolution reaction (HER) and the oxygen reduction reaction (ORR). In this fundamental work, we explored the catalytic properties of TMD family members 2H TaS2 and 1T TaS2 . Our findings reveal that both polytypes exhibit poor HER performance, which is even more pronounced after electrochemical reduction/oxidation. Our experimental data show that 1T TaS2 has a lower overpotential at a current density of -10 mA cm-1 , despite theoretical DFT calculations that indicated that the more favorable free energy of hydrogen adsorption should make "perfect" 2H TaS2 a better HER catalyst. Thorough characterization showed that the higher conductivity of 1T TaS2 and a slightly higher surface oxidation of 2H TaS2 explains this discrepancy. Moreover, changes in the catalytic activity after electrochemical treatment are addressed here. For the ORR in an alkaline environment, the electrochemical treatment led to an improvement in catalytic properties. With onset potentials similar to that of Pt/C catalysts, TaS2 was found to be an efficient catalyst for the ORR, rather than for proton reduction, in contrast to the behavior of Group 6 layered TMDs.
Keywords: oxygen reduction; chalcogens; tantalum; hydrogen evolution; electrochemistry